Pengaruh Insentif Individu Terhadap Kinerja Karyawan PT. Summit Oto Finance Bitung - Rifai, Iskandar; Rantung, Ventje; Rumawas, Wehelmina (JURNAL ILMIAH SOCIETY, 2016)
This research aims to: Analyze how incentives affect individual performance of employees of PT. Summit Auto finance Bitung. This research is a survey while the methods used is the method that emphasizes research on the excavation of ideas and things - things other details attached to a phenomenon The research was carried on in PT. Summit Oto Finance Bitung. The results of this study may show no significant effect between individual incentives with the performance of employees at PT Summit Oto Finance Bitung because the incentive is too small, so the incentives of individuals from the perspective of employees is low. So based research company must still provide an incentive to add more number of individuals and individual incentives in order to get a positive response from employees. Keywords: Incentives affect individual , Performance